Analysis of factors that influence the learning of a foreign language writing - Mabel Anastasia Acosta García; Daniel González González (Universidad de Granada, 2012)
This study was designed to assess the influence of motivational variables, learning styles and learning strategies in the development of writing skills in English of students from first to second years at the University of Ciego de Avila. To achieve that objective was used the following questionnaires: R _SPQ_ 2 F to assess the level of motivation of the students towards the English, (CHAEA) to determine the learning styles of the sample, the Assessment Questionnaire Learning Strategies for determine the strategies used in learning English, and a writing test where students wrote a letter to a foreign friend telling them about your country, to assess the level of writing skills. Our results confirm the hypothesis proposed earlier: when the deep motivation level is higher than the motivation level surface is achieved further development of writing skills, students with a balanced profile between four learning styles get a higher level of development in writing and, when all students develop learning strategies or more of them get further development in writing.